PENINGKATAN AKTIVITAS DAN HASIL BELAJAR KETERAMPILAN KERAJINAN DENGAN MENGGUNAKAN PENDEKATAN PEMBELAJARANKOOPERATIF TIPE STAD DI KELAS VII SMP N 3 KUBUNG - AKHDARIATI, Dr.Ramalis Hakim, M.Pd. Drs. Efrizal, M.Pd (Serupa The Journal of Art Education, 2014)
This research is motivated by the lack of student learning outcomes in making handicraft skills and students tend to be lazy when learning skills, do not bring material and tool skills, students do not understand the work in the group. This study aims to improve student learning outcomes in making the craft skills of artificial materials is by using STAD cooperative learning model. This research is research class action, the research was conducted on half of January to June 2014 class VII SMP N 3 lemur solok district with the number 19 in the learning material making crafts artificial ingredients. This classroom action research carried out by 2 cycles. For the observed ability is the result of learning the craft skills of artificial materials in the first cycle is averaging 76.11. While in the second cycle of learning outcomes mengg craft skills with artificial materials using cooperative learning model STAD increased by an average of 82.84. So, skill kerjinan artificial materials using cooperative learning model STAD in class VII SMP N 3 Kubung Solok successfully and can improve student learning outcomes. The results of this study indicate that the use of cooperative learning model STAD can improve student learning outcomes in making handicraft artificial ingredients. This is evident from the increase in learning outcomes of each cycle are executed.Keywords: Results of learning, craft skills, approach STAD